2014
DOI: 10.2147/jmdh.s67252
|View full text |Cite
|
Sign up to set email alerts
|

Five-year tracking of Plasmodium falciparum allele frequencies in a holoendemic area with indistinct seasonal transitions

Abstract: BackgroundThe renewed malaria eradication efforts require an understanding of the seasonal patterns of frequency of polymorphic variants in order to focus limited funds productively. Although cross-sectional studies in holoendemic areas spanning a single year could be useful in describing parasite genotype status at a given point, such information is inadequate in describing temporal trends in genotype polymorphisms. For Plasmodium falciparum isolates from Kisumu District Hospital, Plasmodium falciparum chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…of 76T CQR allele AF PCTrends in prev. of 86Y CQR allele AF PCAndriantsoanirina et al [37]18.7 nM (95% CI 14.7–23.7 nM)Madagascar2005NRNRAchieng et al [19]NRKenya19992008–2014: 28.5%, 2014: 2.3%2008–2014: 14.9%Hemming-Schroeder et al [20]NRKenya1999Kakamega2003: 80%2005: 61%2008: 60%2015: 2.7%Kombewa2003: 71%2005: 91.9%2008: 90%2015: 11.8%Kakamega2003: 59.2%2005: 59.1%2008: 40%2015: 4.2%Kombewa2003: 57.1%2005: 40%2008: 45%2015: 5%Akala et al [46]NRKenya19992008: 68.4%2009: 55.4%2010: 47.8%2011: 12.4%2012: 29.8%2008: 38.1%2009: 24.3%2010: 19.7%2011: 7.8%2012: 13.3%Lucchi et al [22]2010: 31.77 nM2011: 23.42 nM2012: 21.09 nM2013: 19.85 nMKenya19992010: 38.8%2011: 28.6%2012: 18.7%2013: 7%2010: 2%2011: 1.5%2012: 0%2013: 0%Okombo et al [18]NRKenya19992006: 49.5%2013: 17.2%2006: 57.5%2013: 2.1%Mwai et al [21]63 ± 90 nM (5-150 nM)Kenya19991993–2006: 94% to 63%1993–2006: 75%Bo Huang et al [35]NRGrande Comore Island20042006–2014: 72.2–19.5%2006–2007: 87%2013–2014: 40.2%Das et al [28]Kolkata2013: 238.6 nM, (95% CI 121–321 nM)Purulia2013: 247.42 nM, (95% CI 126–316 nM)India1982Kolkata2012: 94.64%Purulia2012: 96.15%K...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…of 76T CQR allele AF PCTrends in prev. of 86Y CQR allele AF PCAndriantsoanirina et al [37]18.7 nM (95% CI 14.7–23.7 nM)Madagascar2005NRNRAchieng et al [19]NRKenya19992008–2014: 28.5%, 2014: 2.3%2008–2014: 14.9%Hemming-Schroeder et al [20]NRKenya1999Kakamega2003: 80%2005: 61%2008: 60%2015: 2.7%Kombewa2003: 71%2005: 91.9%2008: 90%2015: 11.8%Kakamega2003: 59.2%2005: 59.1%2008: 40%2015: 4.2%Kombewa2003: 57.1%2005: 40%2008: 45%2015: 5%Akala et al [46]NRKenya19992008: 68.4%2009: 55.4%2010: 47.8%2011: 12.4%2012: 29.8%2008: 38.1%2009: 24.3%2010: 19.7%2011: 7.8%2012: 13.3%Lucchi et al [22]2010: 31.77 nM2011: 23.42 nM2012: 21.09 nM2013: 19.85 nMKenya19992010: 38.8%2011: 28.6%2012: 18.7%2013: 7%2010: 2%2011: 1.5%2012: 0%2013: 0%Okombo et al [18]NRKenya19992006: 49.5%2013: 17.2%2006: 57.5%2013: 2.1%Mwai et al [21]63 ± 90 nM (5-150 nM)Kenya19991993–2006: 94% to 63%1993–2006: 75%Bo Huang et al [35]NRGrande Comore Island20042006–2014: 72.2–19.5%2006–2007: 87%2013–2014: 40.2%Das et al [28]Kolkata2013: 238.6 nM, (95% CI 121–321 nM)Purulia2013: 247.42 nM, (95% CI 126–316 nM)India1982Kolkata2012: 94.64%Purulia2012: 96.15%K...…”
Section: Resultsmentioning
confidence: 99%
“…A high proportion, 65.8% (25/38) of the studies reported occurrence of mixed genotype infections. Six studies reported mixed 76T/86Y infections (Indonesia: [ 45 ]; India: [ 41 ]; Kenya: [ 46 ]; Benin: [ 23 ]; Mozambique: [ 16 ]). Thirteen studies reported presence of 76T/K and 86Y/N genotype in P. falciparum infections.…”
Section: Resultsmentioning
confidence: 99%
“…Since effective vaccines for malaria are still way off, and drugs are most relied upon, success of malaria control strategies are dependent on understanding factors that influence dispersion of malaria drug resistance genotypes. Most studies on CQR appear inconclusive on methods of containing it's spread due to insufficient demographic and clinical information (Akala et al, 2014;Angira, Otieno, Muga, & Abong'o, 2010;Zhong et al, 2008). This study showed that travel, gender and clinical factors were associated with chloroquine resistance among symptomatic malaria cases in four of the five malaria epidemic zones in Kenya.…”
Section: Discussionmentioning
confidence: 76%
“…However, in endemic regions, males may delay seeking treatment and risk accumulating super infection. Research has shown that mutant strains that develop drug resistance enhance virulence (Shahinas, Folefoc, & Pillai, 2013) wanton utilization of resources and therefore eliciting symptoms that distorts the host/parasite balance that would allow wild type parasites to remain asymptomatic (Akala et al, 2014;Deroost, Pham, Opdenakker, & Van den Steen, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The division of experimental therapeutics of the WRAIR supplied the following drugs: chloroquine diphosphate (CQ), dihydroartemisinin (DHA), artemether (AT), mefloquine (MQ) and lumefantrine (LU). SYBR green I assay technique [ 18 ] with additional modification [ 19 ] was used for drug susceptibility testing of the parasites. Drugs were dissolves in dimethyl sulfoxide before performing a 2-fold serial dilution in tissue culture media to dose ranges of DHA (700 nM to 0.69 nM), LU (378 nM to 0.37 nM), MQ (1200 nM to 1.1 nM), AT (670 nM to 0.65 nM) and CQ (883 nM to 3.79 nM); 3.2 μL of the drug diluents were aliquoted into 384-well plates.…”
Section: Methodsmentioning
confidence: 99%